Environmentally friendly waterproof grouting material

By using modified waterproof gel particles and dense waterproof gel layer in the grouting material, the problem of cracking of the waterproof layer of the grouting material is solved, high waterproof and reinforcement effects are achieved, and high waterproof needs are met.

CN116514497BActive Publication Date: 2024-12-27LUJIANG XINCHUANG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211712382.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2024-12-27
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

The existing grouting material is prone to rupture after time, and cannot effectively fill the cracks, resulting in weakening of the waterproofing effect and difficult to meet the high waterproofing needs.

Method used

Using composite cement, fly ash, mineral powder, aggregate and modified waterproof gel particles, a dense waterproof gel layer is formed through processing, cracks are filled and a waterproof barrier layer is built to enhance the density and waterproof performance of the grouting material. .

Benefits of technology

It achieves high waterproofing effect, inhibits moisture infiltration, and improves the acid and alkali resistance and compression resistance of the grouting material, extending the durability of the waterproofing effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004027922640000121
    Figure BDA0004027922640000121
  • Figure BDA0004027922640000131
    Figure BDA0004027922640000131
Patent Text Reader

Abstract

The present invention relates to the technical field of building engineering materials, and in particular to an environmentally friendly waterproof grouting material, comprising the following raw material components by weight: 100-150 parts of composite cement, 20-30 parts of fly ash, 10-20 parts of mineral powder, 50-70 parts of aggregate, 8-13 parts of waterproof gel particles, and 3-8 parts of admixture. The waterproof grouting material of the present invention is prepared by adding waterproof gel particles on the basis of conventional raw materials, and processing the waterproof gel particles. After grouting, the modified waterproof gel particles contained in the grouting material can not only fill the cracks formed in the grouting material, improve the compactness of the grouting material, thereby enhancing its strength, but also construct a barrier waterproof gel layer in the grouting material, thereby effectively inhibiting the infiltration of water and achieving a high waterproof effect, and at the same time, it can also hinder the penetration of corrosive media and improve its acid and alkali resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building engineering materials, in particular to an environmentally friendly waterproof grouting material. Background Art

[0002] Grouting, also known as grouting, is a process of preparing certain materials into slurry and injecting it into strata or fissures using grouting equipment to expand, gel or solidify it, so as to achieve the purpose of reinforcing surrounding rock or preventing seepage. The flow process of grouting slurry is the result of the combined action of slurry and injected medium. Since the engineering rock mass is under complex hydrogeological conditions such as weak seepage, the existing fracture penetration grouting materials and grouting theories are difficult to meet the actual engineering needs. The selection of grouting materials is one of the key conditions for surrounding rock anti-seepage, especially for projects such as urban underground space, which has very important practical significance.

[0003] For example, the invention patent with announcement number CN107235688A discloses a waterproof grouting material behind a GIL integrated pipe gallery and a grouting method thereof. A waterproof layer is formed on the surface of the grouting material by adding a waterproof emulsion, thereby achieving a waterproof effect. Since the waterproof layer is formed on the surface of the grouting material, although it can have a good waterproof effect during cast-in-place, as time goes by, the waterproof layer is easily affected by external factors and cracks, resulting in a weakening of the waterproof effect. Moreover, after the grouting material hardens, cracks are easily formed inside, and the cracks will gradually increase under the action of stress. Since the waterproof layer cannot fill the cracks, the cracks will damage the waterproof layer while increasing, thereby failing to meet the high waterproof operation requirements. Summary of the invention

[0004] The purpose of the present invention is to provide an environmentally friendly waterproof grouting material, which can effectively inhibit the infiltration of water and achieve a high waterproof effect by filling cracks formed in the grouting material and constructing a waterproof gel layer in the grouting material.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] An environmentally friendly waterproof grouting material comprises the following raw material components in parts by weight: 100-150 parts of composite cement, 20-30 parts of fly ash, 10-20 parts of mineral powder, 50-70 parts of aggregate, 8-13 parts of waterproof gel particles, and 3-8 parts of admixture;

[0007] Among them, the preparation method of waterproof grouting material is as follows:

[0008] Weigh each raw material component by weight, process the waterproof gel particles to obtain modified waterproof gel particles, and pour them into the silo together with composite cement, fly ash, mineral powder, aggregate and admixtures, stir evenly to obtain a mixture, and then pour the mixture into the mixing bucket of the mixing and conveying integrated machine, connect the soft water pipe to the water injection port of the mixing and conveying integrated machine, and connect the other end to the water source joint at the construction site. According to the water demand requirements, add the required amount of water through the liquid flow meter, add the required amount of water to the dry mixture in the mixing and grouting integrated machine, and stir continuously for 2-3 minutes to obtain the required grouting material;

[0009] The processing of the waterproof gel particles specifically includes the following steps:

[0010] 1) Add hexadecyltrimethylammonium bromide, distilled water, tetrahydrate chloroauric acid and sodium citrate solution into a container in sequence, stir and mix them thoroughly in a water bath at 30-35° C., then quickly add sodium borohydride solution, continue stirring for 2-5 minutes and let stand for 3-6 hours to obtain a seed solution;

[0011] 2) Add hexadecyltrimethylammonium bromide, distilled water, tetrahydrate chloroauric acid and silver nitrate solution to a container in sequence, stir and mix them in a water bath at 30-35° C., then add ascorbic acid solution and waterproof gel particles, stir them thoroughly, quickly add seed solution, continue to stand in a water bath for 12-16 hours, centrifuge, wash, and freeze-dry to obtain modified waterproof gel particles.

[0012] As a further preferred embodiment of the present invention, in the seed solution, the usage ratio of hexadecyltrimethylammonium bromide, distilled water, tetrahydrate chloroauric acid, sodium citrate solution and sodium borohydride solution is (3-5) g: (95-120) mL: (2.5-3.0) mL: (5-8) mL: (0.5-0.8) mL;

[0013] The concentration of the tetrahydrate chloroauric acid is 10-16 mmol / L;

[0014] The concentration of the sodium citrate solution is 10-16 mmol / L;

[0015] The concentration of the sodium borohydride solution is 10-13 mmol / L.

[0016] As a further preferred embodiment of the present invention, the usage ratio of hexadecyltrimethylammonium bromide, distilled water, tetrahydrate chloroauric acid, silver nitrate solution, ascorbic acid solution, waterproof gel particles and seed solution is (3.5-4.0) g: (93-100) mL: (5.2-6.3) mL: (1.0-1.5) mL: (0.6-1.0) mL: (2-5) g: (1.6-2.3) mL;

[0017] The concentration of the silver nitrate solution is 10-16 mmol / L;

[0018] The concentration of the ascorbic acid solution is 0.1-0.2 mol / L.

[0019] As a further preferred embodiment of the present invention, the composite cement is composed of silicate cement and sulphoaluminate cement in a mass ratio of 1:(1-3);

[0020] The admixture is composed of a water reducer, a thickener, a defoamer, and a retarder in a mass ratio of 1: (0.5-0.9): (0.3-0.6): (1.2-1.8);

[0021] The grade of the fly ash is not lower than that of the second-grade fly ash, and the fineness is 500-1500 mesh;

[0022] The mineral powder is composed of S95 grade mineral powder and S75 grade mineral powder in a mass ratio of 1:(0.3-0.6);

[0023] The aggregate is composed of quartz sand with three different particle sizes of 0.5-1.0 mm, 1-2 mm and 2-4 mm in a mass ratio of 1: (0.2-0.5): (1.2-1.7).

[0024] As a further preferred embodiment of the present invention, the preparation method of the waterproof gel particles is as follows:

[0025] 1) adding laponite to deionized water, stirring thoroughly to obtain a dispersion, adding acrylamide, methacryloxypropyltrimethoxysilane, α-methacrylic acid, ethylene glycol dimethacrylate and potassium persulfate in sequence, and mixing thoroughly to obtain a composite gel solution;

[0026] 2) Add the nanosheet composite material to the composite gel solution, transfer it to a deoxygenated aging tank after ultrasonic dispersion, seal it and react for 45-50 hours. After the reaction is completed, take out the product, crush it, and freeze-dry it to obtain waterproof gel particles.

[0027] As a further preferred embodiment of the present invention, in the composite gel solution, the usage ratio of laponite, deionized water, acrylamide, methacryloxypropyltrimethoxysilane, α-methacrylic acid, ethylene glycol dimethacrylate and potassium persulfate is (1-5) g: (100-160) mL: (18-26) g: (3-6) g: (10-15) g: (0.3-0.7) g: (0.1-0.3) g.

[0028] As a further preferred embodiment of the present invention, the mass volume ratio of the nanosheet composite material to the composite gel solution is 1 g: (30-50) mL;

[0029] The reaction temperature is 60-70°C.

[0030] As a further preferred embodiment of the present invention, the preparation method of the nanosheet composite material is as follows:

[0031] 1) adding lithium fluoride to a hydrochloric acid solution, stirring and dissolving, then adding titanium aluminum carbide, reacting at 35-40° C. for 23-27 hours, repeatedly washing the obtained product with deionized water, dispersing the precipitate in a sufficient amount of deionized water, ultrasonically treating in an argon atmosphere for 30-50 minutes, and removing the lower precipitate after centrifugation to obtain multilayer titanium carbide particles;

[0032] 2) Dispersing the multilayer titanium carbide particles in deionized water to obtain a dispersion, adding sodium hydroxide to the dispersion, stirring and reacting at room temperature for 24-30 hours, and after the reaction is completed, repeatedly washing with deionized water and freeze-drying to obtain a nanosheet composite material.

[0033] As a further preferred embodiment of the present invention, the ratio of the lithium fluoride, the hydrochloric acid solution and the titanium aluminum carbide is (1-3) g: (20-30) mL: (1-3) g;

[0034] The concentration of the hydrochloric acid solution is 9-10 mol / L;

[0035] The power of the ultrasonic treatment is 100-200W;

[0036] The centrifugal speed is 4000-5000r / min, and the centrifugal time is 30-40min;

[0037] The dispersion concentration is 3-8 mg / L;

[0038] The dosage ratio of the sodium hydroxide to the dispersion is (3.2-4.0) g: (40-60) mL.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] In the present invention, methacryloxypropyltrimethoxysilane is used as a silicon source, hectorite is used as a toughening agent and an inorganic crosslinking agent, and ethylene glycol dimethacrylate is used as an organic crosslinking agent, which are matched with acrylamide and α-methacrylic acid to form a composite gel solution, and a nanosheet composite material is added to form waterproof gel particles through polymerization; wherein, acrylamide and α-methacrylic acid monomers are polymerized to form a dense three-dimensional grid structure, which has excellent viscoelasticity and temperature resistance, can be deformed when subjected to pressure, and enter into smaller gaps in the grouting material to fill the gaps, thereby improving the density of the internal structure of the grouting material, thereby inhibiting the infiltration of water and achieving a waterproof effect. At the same time, in order to prevent the waterproof gel particles from collapsing due to the large deformation amount when subjected to external force, thereby affecting the waterproof effect, in the present invention, the nanosheet composite material is introduced into the waterproof gel particles to further improve their compression resistance, thereby reducing their deformation amount. The rice sheet composite material uses titanium aluminum carbide as a raw material. After low-power and short-time ultrasonic treatment, impurities in titanium aluminum carbide are removed to obtain unpeeled multi-layer titanium dicarbide particles, which are used as a precursor and etched in an alkaline solution for a long time. Due to the low concentration of the alkaline solution, the etching effect on the precursor is weak, thereby obtaining a nanosheet composite material whose surface is etched into a nanowire structure and the main body is still a multi-layer sheet structure. The nanosheet composite material is inside the waterproof gel particles. Through the mutual entanglement and cross-linking of the nanowire structure, while constructing a cross-linked network structure, it also shortens the spacing of the multi-layer sheet structure, so that the multi-layer sheet structures can be interlaced to form connection points, thereby enhancing the overall stability of the cross-linked network structure, so that a new high-stability cross-linked network is constructed inside the waterproof gel particles, which effectively improves the resistance of the waterproof gel particles to external forces, so that when they are squeezed by external forces, the deformation amount can be effectively controlled and the structure will not collapse.

[0041] In order to further improve the waterproof effect of the grouting material, the waterproof gel particles are processed in the present invention, and the waterproof gel particles are used as a matrix, and a nanorod layer is deposited on the surface thereof to obtain modified waterproof gel particles. When subjected to external force, the modified waterproof gel particles collide and squeeze with each other, and the nanorods deposited on the surface are cross-stacked to form a connector, so that the modified waterproof gel particles are connected to each other to form a three-dimensional gel layer. Since the modified waterproof gel particles have good deformation ability, when the nanorods are cross-stacked, the modified waterproof gel particles are squeezed by external force in all directions and change from the original sphere to a cube, so that the modified waterproof gel particles are connected to each other, and each surface abuts against each other to form a dense interface, thereby constructing a densely connected gel layer. The dense and continuous gel layer can play the role of a waterproof barrier layer in the grouting material, thereby further reducing the infiltration of water, thereby achieving a high waterproof effect of the grouting material.

[0042] The waterproof grouting material of the present invention is prepared by adding waterproof gel particles to conventional raw materials and processing the waterproof gel particles. After grouting, the modified waterproof gel particles contained in the grouting material can not only fill the cracks formed in the grouting material, improve the density of the grouting material, and thus enhance its strength, but also construct a barrier waterproof gel layer in the grouting material, thereby effectively inhibiting the infiltration of water and achieving a high waterproof effect. At the same time, it can also hinder the penetration of corrosive media and improve its acid and alkali resistance. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] In the embodiment of the present invention, the composite cement is composed of silicate cement and sulphoaluminate cement in a mass ratio of 1:2;

[0045] The admixture is composed of water reducer, thickener, defoamer and retarder in a mass ratio of 1:0.5:0.3:1.4;

[0046] The grade of fly ash shall not be lower than Grade II fly ash, and the fineness shall be 1000 mesh;

[0047] The mineral powder is composed of S95 grade mineral powder and S75 grade mineral powder in a mass ratio of 1:0.3;

[0048] The aggregate is composed of quartz sand with three different particle sizes of 0.5-1.0mm, 1-2mm and 2-4mm in a mass ratio of 1:0.2:1.6.

[0049] In the embodiment of the present invention, the water reducing agent is melamine sulfonate formaldehyde condensation polymer, the thickener is carboxymethyl cellulose, the defoaming agent is polyoxypropylene glycerol ether, and the retarder is sodium lignin sulfonate.

[0050] Example 1

[0051] An environmentally friendly waterproof grouting material, characterized in that it comprises the following raw material components in parts by weight: 100 parts of composite cement, 20 parts of fly ash, 10 parts of mineral powder, 50 parts of aggregate, 8 parts of waterproof gel particles, and 3 parts of admixture;

[0052] Among them, the preparation method of waterproof grouting material is as follows:

[0053] Weigh each raw material component by weight, process the waterproof gel particles to obtain modified waterproof gel particles, and pour them into the silo together with composite cement, fly ash, mineral powder, aggregate and admixtures, stir evenly to obtain a mixture, and then pour the mixture into the mixing bucket of the mixing and conveying integrated machine, connect the soft water pipe to the water injection port of the mixing and conveying integrated machine, and connect the other end to the water source joint at the construction site. According to the water demand requirements, add the required amount of water through the liquid flow meter, add the required amount of water to the dry mixture in the mixing and grouting integrated machine, and stir continuously for 2 minutes to obtain the required grouting material;

[0054] The processing of the waterproof gel particles specifically includes the following steps:

[0055] 1) 3 g of hexadecyltrimethylammonium bromide, 95 mL of distilled water, 2.5 mL of 10 mmol / L chloroauric acid tetrahydrate, and 5 mL of 10 mmol / L sodium citrate solution were sequentially added into a container, stirred and mixed thoroughly in a 30°C water bath, and then 0.5 mL of 10 mmol / L sodium borohydride solution was quickly added, and the mixture was stirred for 2 min and allowed to stand for 3 h to obtain a seed solution;

[0056] 2) 3.5 g of hexadecyltrimethylammonium bromide, 93 mL of distilled water, 5.2 mL of 10 mmol / L tetrahydrate chloroauric acid and 1.0 mL of 10 mmol / L silver nitrate solution were added to the container in sequence, and the mixture was stirred thoroughly in a 30°C water bath. Subsequently, 0.6 mL of 0.1 mol / L ascorbic acid solution and 2 g of waterproof gel particles were added. After stirring thoroughly, 1.6 mL of seed solution was quickly added, and the mixture was allowed to stand in the water bath for 12 h. After centrifugation and washing, the mixture was freeze-dried to obtain modified waterproof gel particles.

[0057] Wherein, the preparation method of waterproof gel particles is as follows:

[0058] 1) adding 1 g of hectorite to 100 mL of deionized water, stirring thoroughly to obtain a dispersion, adding 18 g of acrylamide, stirring thoroughly to obtain a mixed dispersion, adding 3 g of methacryloxypropyltrimethoxysilane and 10 g of α-methacrylic acid in sequence, stirring thoroughly, adding 0.3 g of ethylene glycol dimethacrylate and 0.1 g of potassium persulfate, and mixing thoroughly to obtain a composite gel solution;

[0059] 2) The nanosheet composite material was added to the composite gel solution at a mass volume ratio of 1 g:30 mL, ultrasonically dispersed at 300 W for 10 min, and then transferred to a deoxygenated aging tank, sealed and reacted at 60° C. for 45 h. After the reaction was completed, the product was taken out and crushed and freeze-dried to obtain waterproof gel particles.

[0060] The above-mentioned method for preparing the nanosheet composite material is as follows:

[0061] 1) adding 1 g of lithium fluoride to 20 mL of 9 mol / L hydrochloric acid solution, stirring thoroughly until completely dissolved, then adding 1 g of titanium aluminum carbide, reacting at 35° C. for 23 h, repeatedly washing the obtained product with deionized water, dispersing the precipitate in sufficient deionized water, ultrasonically treating at 100 W for 30 min in an argon atmosphere, centrifuging at 4000 r / min for 30 min, removing the lower precipitate, and obtaining multilayer titanium carbide particles;

[0062] 2) The multilayer titanium carbide particles are dispersed in deionized water to obtain a dispersion with a concentration of 3 mg / L, 3.2 g of sodium hydroxide is added to 40 mL of the dispersion, and the mixture is stirred at 100 r / min at room temperature for 24 h. After the reaction is completed, the nanosheet composite material is repeatedly washed with deionized water and freeze-dried.

[0063] Example 2

[0064] An environmentally friendly waterproof grouting material, characterized in that it comprises the following raw material components by weight: 120 parts of composite cement, 25 parts of fly ash, 15 parts of mineral powder, 60 parts of aggregate, 10 parts of waterproof gel particles, and 5 parts of admixture;

[0065] Among them, the preparation method of waterproof grouting material is as follows:

[0066] Weigh each raw material component by weight, process the waterproof gel particles to obtain modified waterproof gel particles, and pour them into the silo together with composite cement, fly ash, mineral powder, aggregate and admixture, stir evenly to obtain a mixture, and then pour the mixture into the mixing bucket of the mixing and conveying integrated machine, connect the soft water pipe to the water injection port of the mixing and conveying integrated machine, and connect the other end to the water source joint at the construction site, add the required amount of water through the liquid flow meter according to the water demand requirements, add the required amount of water to the dry mixture in the mixing and grouting integrated machine, and stir continuously for 3 minutes to obtain the required grouting material;

[0067] The processing of the waterproof gel particles specifically includes the following steps:

[0068] 1) 4 g of hexadecyltrimethylammonium bromide, 100 mL of distilled water, 3 mL of 15 mmol / L chloroauric acid tetrahydrate, and 7 mL of 15 mmol / L sodium citrate solution were sequentially added into a container, stirred and mixed thoroughly in a 32°C water bath, and then 0.7 mL of 12 mmol / L sodium borohydride solution was quickly added, and the mixture was stirred for 4 min and allowed to stand for 5 h to obtain a seed solution;

[0069] 2) 3.7 g of hexadecyltrimethylammonium bromide, 98 mL of distilled water, 5.6 mL of 15 mmol / L chloroauric acid tetrahydrate and 1.2 mL of 15 mmol / L silver nitrate solution were added to the container in sequence, and the mixture was stirred thoroughly in a 32°C water bath. Subsequently, 0.8 mL of 0.2 mol / L ascorbic acid solution and 3 g of waterproof gel particles were added. After stirring thoroughly, 1.8 mL of seed solution was quickly added, and the mixture was allowed to stand in the water bath for 15 h. After centrifugation and washing, the mixture was freeze-dried to obtain modified waterproof gel particles.

[0070] Wherein, the preparation method of waterproof gel particles is as follows:

[0071] 1) 4 g of hectorite was added to 150 mL of deionized water, and the mixture was stirred thoroughly to obtain a dispersion. 23 g of acrylamide was added, and the mixture was stirred thoroughly to obtain a mixed dispersion. 5 g of methacryloxypropyltrimethoxysilane and 12 g of α-methacrylic acid were added in sequence. After stirring thoroughly, 0.5 g of ethylene glycol dimethacrylate and 0.2 g of potassium persulfate were added, and the mixture was mixed thoroughly to obtain a composite gel solution.

[0072] 2) The nanosheet composite material was added to the composite gel solution at a mass volume ratio of 1 g:40 mL, ultrasonically dispersed at 400 W for 20 min, and then transferred to a deoxygenated aging tank, sealed and reacted at 65° C. for 47 h. After the reaction was completed, the product was taken out and crushed and freeze-dried to obtain waterproof gel particles.

[0073] The above-mentioned method for preparing the nanosheet composite material is as follows:

[0074] 1) Add 2 g of lithium fluoride to 25 mL of 9.5 mol / L hydrochloric acid solution, stir thoroughly until completely dissolved, then add 2 g of titanium aluminum carbide, react at 37° C. for 25 h, wash the obtained product repeatedly with deionized water, disperse the precipitate in sufficient deionized water, treat it with 150 W ultrasound in an argon atmosphere for 40 min, centrifuge it at 4500 r / min for 35 min, remove the lower precipitate, and obtain multilayer titanium carbide particles;

[0075] 2) The multilayer titanium carbide particles are dispersed in deionized water to obtain a dispersion with a concentration of 5 mg / L, 3.8 g of sodium hydroxide is added to 50 mL of the dispersion, and the mixture is stirred at 200 r / min at room temperature for 26 hours. After the reaction is completed, the nanosheet composite material is repeatedly washed with deionized water and freeze-dried.

[0076] Example 3

[0077] An environmentally friendly waterproof grouting material, characterized in that it comprises the following raw material components by weight: 150 parts of composite cement, 30 parts of fly ash, 20 parts of mineral powder, 70 parts of aggregate, 13 parts of waterproof gel particles, and 8 parts of admixture;

[0078] Among them, the preparation method of waterproof grouting material is as follows:

[0079] Weigh each raw material component by weight, process the waterproof gel particles to obtain modified waterproof gel particles, and pour them into the silo together with composite cement, fly ash, mineral powder, aggregate and admixture, stir evenly to obtain a mixture, and then pour the mixture into the mixing bucket of the mixing and conveying integrated machine, connect the soft water pipe to the water injection port of the mixing and conveying integrated machine, and connect the other end to the water source joint at the construction site, add the required amount of water through the liquid flow meter according to the water demand requirements, add the required amount of water to the dry mixture in the mixing and grouting integrated machine, and stir continuously for 3 minutes to obtain the required grouting material;

[0080] The processing of the waterproof gel particles specifically includes the following steps:

[0081] 1) 5 g of hexadecyltrimethylammonium bromide, 120 mL of distilled water, 3 mL of 16 mmol / L tetrahydrate chloroauric acid, and 8 mL of 16 mmol / L sodium citrate solution were sequentially added into a container, stirred and mixed thoroughly in a 35°C water bath, and then 0.8 mL of 13 mmol / L sodium borohydride solution was quickly added, and the mixture was stirred for 5 min and allowed to stand for 6 h to obtain a seed solution;

[0082] 2) 4 g of hexadecyltrimethylammonium bromide, 100 mL of distilled water, 6.3 mL of 16 mmol / L tetrahydrate chloroauric acid and 1.5 mL of 16 mmol / L silver nitrate solution were sequentially added into a container, stirred thoroughly in a 35°C water bath, and then 1.0 mL of 0.2 mol / L ascorbic acid solution and 5 g of waterproof gel particles were added. After sufficient stirring, 2.3 mL of seed solution was quickly added, and the mixture was allowed to stand in a water bath for 16 h. After centrifugation and washing, the mixture was freeze-dried to obtain modified waterproof gel particles.

[0083] Wherein, the preparation method of waterproof gel particles is as follows:

[0084] 1) 5 g of hectorite was added to 160 mL of deionized water, and the mixture was stirred thoroughly to obtain a dispersion. 26 g of acrylamide was added, and the mixture was stirred thoroughly to obtain a mixed dispersion. 6 g of methacryloxypropyltrimethoxysilane and 15 g of α-methacrylic acid were added in sequence. After stirring thoroughly, 0.7 g of ethylene glycol dimethacrylate and 0.3 g of potassium persulfate were added, and the mixture was mixed thoroughly to obtain a composite gel solution.

[0085] 2) The nanosheet composite material was added to the composite gel solution at a mass volume ratio of 1 g:50 mL, ultrasonically dispersed at 500 W for 30 min, and then transferred to a deoxygenated aging tank, sealed and reacted at 70° C. for 50 h. After the reaction was completed, the product was taken out and crushed and freeze-dried to obtain waterproof gel particles.

[0086] The above-mentioned method for preparing the nanosheet composite material is as follows:

[0087] 1) adding 3 g of lithium fluoride to 30 mL of a 10 mol / L hydrochloric acid solution, stirring thoroughly until completely dissolved, then adding 3 g of titanium aluminum carbide, reacting at 40° C. for 27 h, repeatedly washing the obtained product with deionized water, dispersing the precipitate in sufficient deionized water, ultrasonically treating at 200 W for 50 min in an argon atmosphere, centrifuging at 5000 r / min for 40 min, removing the lower precipitate, and obtaining multilayer titanium carbide particles;

[0088] 2) The multilayer titanium carbide particles are dispersed in deionized water to obtain a dispersion with a concentration of 8 mg / L, 4.0 g of sodium hydroxide is added to 60 mL of the dispersion, and the mixture is stirred at 300 r / min for 30 h at room temperature. After the reaction is completed, the nanosheet composite material is repeatedly washed with deionized water and freeze-dried.

[0089] Comparative Example 1: This comparative example is substantially the same as Example 1, except that it does not contain waterproof gel particles.

[0090] Comparative Example 2: This comparative example is basically the same as Example 1, except that the waterproof gel particles are not processed during use.

[0091] Comparative Example 3: This comparative example is basically the same as Example 1, except that no nanosheet composite material is added during the preparation of the waterproof gel particles.

[0092] Comparative Example 4: This comparative example is basically the same as Example 1, except that, in the preparation process of the waterproof gel particles, multilayer titanium carbide particles are used instead of the nanosheet composite material.

[0093] Comparative Example 5: This comparative example is basically the same as Example 1, except that, during the preparation of the nanosheet composite material, 500 W ultrasonic treatment for 2 h was used instead of 100 W ultrasonic treatment for 30 min.

[0094] Test experiment:

[0095] (I) Experimental preparation: grouting materials provided by Examples 1-3 and Comparative Examples 1-5, 1 tensile tester, 1 waterproof tester, 1 mortar press, 1 balance, 8 150㎜×150㎜×10㎜ mold boxes, multiple 500ml conical measuring cylinders, 3 1000ml containers, 500ml each of 10% sodium hydroxide solution and 1% hydrochloric acid solution, 3 70㎜×70㎜×70㎜ test molds, 2kg each of coarse sand and gravel.

[0096] (II) Sample preparation: Pour the grouting material prepared in Example 1 into two mold boxes, and the remaining part is directly used for performance test 4; after the grouting material in the mold box is solidified, it is taken out from the mold box and cut into several 50mm×20mm×10mm long strip test pieces. The grouting materials of Examples 2 to 4 are treated in the same way.

[0097] (III) Performance test:

[0098] 1. Waterproof test: Insert the test piece of each sample into the watertight instrument, open the water injection valve and keep the pressure at 0.2MPa for 30 minutes, observe whether each test piece is water-permeable and record it.

[0099] 2. Durability test: Soak the test pieces of each sample in 10% sodium hydroxide solution and 1% hydrochloric acid solution for 72 hours, take them out, observe whether there is powdering or cracking on the surface of each test piece, and record them.

[0100] 4. Strength test: Weigh an appropriate amount of the mixed grouting material to be tested for each sample, pour it into a 70mm×70mm×70mm test mold for solidification, take out the solidified grouting material and put it into a mortar press, gradually pressurize until the specimen is destroyed, and record the compressive strength;

[0101] Weigh an appropriate amount of the mixed grouting material to be tested in each embodiment, pour it into a 70mm×70mm×70mm test mold filled with sand and gravel for solidification, take out the solidified grouting material and put it into a mortar press, gradually pressurize it until the specimen is destroyed, and record the consolidation strength.

[0102] (IV) Test results:

[0103] The test results are shown in Table 1.

[0104] Table 1

[0105]

[0106]

[0107] It can be seen from Table 1 that the waterproof grouting material in the present invention can maintain excellent waterproof performance under large water volume and strong pressure, and meets the technical requirements of both waterproofing and reinforcement functions.

[0108] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An environmentally friendly waterproof grouting material, characterized in that: The raw material components include the following parts by weight: 100-150 parts of composite cement, 20-30 parts of fly ash, 10-20 parts of mineral powder, 50-70 parts of aggregate, 8-13 parts of waterproof gel particles, and 3-8 parts of admixture. The preparation method of the waterproof gel particles is as follows: 1) adding laponite to deionized water, stirring thoroughly to obtain a dispersion, adding acrylamide, methacryloxypropyltrimethoxysilane, α-methacrylic acid, ethylene glycol dimethacrylate and potassium persulfate in sequence, and mixing thoroughly to obtain a composite gel solution; 2) Add the nanosheet composite material to the composite gel solution, transfer it to a deoxygenated aging tank after ultrasonic dispersion, seal it and react for 45-50 hours. After the reaction is completed, take out the product, crush it, and freeze-dry it to obtain waterproof gel particles. In the composite gel solution, the usage ratio of laponite, deionized water, acrylamide, methacryloxypropyltrimethoxysilane, α-methacrylic acid, ethylene glycol dimethacrylate and potassium persulfate is (1-5) g: (100-160) mL: (18-26) g: (3-6) g: (10-15) g: (0.3-0.7) g: (0.1-0.3) g, The mass volume ratio of the nanosheet composite material to the composite gel solution is 1g: (30-50)mL; the reaction temperature is 60-70°C, The preparation method of the nanosheet composite material is as follows: 1) Add lithium fluoride to a hydrochloric acid solution, stir and dissolve, then add titanium aluminum carbide, react at 35-40°C for 23-27h, wash the obtained product repeatedly with deionized water, disperse the precipitate in a sufficient amount of deionized water, ultrasonically treat in an argon atmosphere for 30-50min, remove the lower precipitate after centrifugation, and obtain multilayer titanium carbide particles; 2) Dispersing multilayer titanium carbide particles in deionized water to obtain a dispersion, adding sodium hydroxide to the dispersion, stirring the dispersion at room temperature for 24-30 hours, and after the reaction is completed, repeatedly washing with deionized water and freeze-drying to obtain a nanosheet composite material. The ratio of the lithium fluoride, hydrochloric acid solution and titanium aluminum carbide is (1-3) g: (20-30) mL: (1-3) g; The concentration of the hydrochloric acid solution is 9-10 mol / L; The power of the ultrasonic treatment is 100-200W; The centrifugal speed is 4000-5000r / min, and the centrifugal time is 30-40min; The dispersion concentration is 3-8 mg / L; The ratio of the sodium hydroxide to the dispersion is (3.2-4.0) g: (40-60) mL; The preparation method of the waterproof grouting material is as follows: Weigh each raw material component by weight, process the waterproof gel particles to obtain modified waterproof gel particles, and pour them into the silo together with composite cement, fly ash, mineral powder, aggregate and admixtures, stir evenly to obtain a mixture, and then pour the mixture into the mixing bucket of the mixing and conveying integrated machine, connect the soft water pipe to the water injection port of the mixing and conveying integrated machine, and connect the other end to the water source joint at the construction site. According to the water demand requirements, add the required amount of water through the liquid flow meter, add the required amount of water to the dry mixture in the mixing and grouting integrated machine, and stir continuously for 2-3 minutes to obtain the required grouting material; The processing of the waterproof gel particles specifically includes the following steps: 1) Add hexadecyltrimethylammonium bromide, distilled water, tetrahydrate chloroauric acid and sodium citrate solution into a container in sequence, stir and mix thoroughly in a 30-35°C water bath, then quickly add sodium borohydride solution, continue stirring for 2-5 minutes and let stand for 3-6 hours to obtain seed solution; 2) Add hexadecyltrimethylammonium bromide, distilled water, tetrahydrate chloroauric acid and silver nitrate solution to the container in sequence, stir and mix them thoroughly in a water bath at 30-35°C, then add ascorbic acid solution and waterproof gel particles, stir thoroughly, quickly add seed solution, continue to stand in the water bath for 12-16 hours, centrifuge, wash, and freeze-dry to obtain modified waterproof gel particles. In the seed solution, the usage ratio of hexadecyltrimethylammonium bromide, distilled water, tetrahydrate chloroauric acid, sodium citrate solution and sodium borohydride solution is (3-5) g: (95-120) mL: (2.5-3.0) mL: (5-8) mL: (0.5-0.8) mL; The concentration of the tetrahydrate chloroauric acid is 10-16 mmol / L; The concentration of the sodium citrate solution is 10-16 mmol / L; The concentration of the sodium borohydride solution is 10-13 mmol / L, The usage ratio of hexadecyltrimethylammonium bromide, distilled water, tetrahydrate chloroauric acid, silver nitrate solution, ascorbic acid solution, waterproof gel particles and seed solution is (3.5-4.0) g: (93-100) mL: (5.2-6.3) mL: (1.0-1.5) mL: (0.6-1.0) mL: (2-5) g: (1.6-2.3) mL; The concentration of the silver nitrate solution is 10-16 mmol / L; The concentration of the ascorbic acid solution is 0.1-0.2 mol / L.

2. The environmentally friendly waterproof grouting material according to claim 1, characterized in that: The composite cement is composed of silicate cement and sulphoaluminate cement in a mass ratio of 1:(1-3); The admixture is composed of a water reducer, a thickener, a defoamer, and a retarder in a mass ratio of 1: (0.5-0.9): (0.3-0.6): (1.2-1.8); The grade of the fly ash is not lower than that of the second-grade fly ash, and the fineness is 500-1500 mesh; The mineral powder is composed of S95 grade mineral powder and S75 grade mineral powder in a mass ratio of 1: (0.3-0.6); The aggregate is composed of quartz sand with three different particle sizes of 0.5-1.0 mm, 1-2 mm and 2-4 mm in a mass ratio of 1: (0.2-0.5): (1.2-1.7).